Demanda de oxigênio da mineralização de detritos refratários de macrófitas aquáticas - Sciessere, Luciana (2007)
This study evaluated the oxygen demand in the mineralization of Cyperus giganteus and Salvinia auriculata coleted in Óleo lagoon (21º 26' S e 47º 49' W), Luiz Antonio, SP. The C. giganteus experiment assayed the detritus age influence over the oxygen consumption during the decomposition process; besides the detritus age, the S. auriculata experiment evaluated the influence of the presence of sediment as a source of nutrients and microorganisms, and the presence of oxygen during the previous decomposition. Incubations were prepared using lagoon water and macrophytes samples, which were maintained under controlled conditions: 20 ºC, in the dark, and in aerobic environment. The results of the C. giganteus experiment indicated that the aerobic mineralization processes of the integral detritus consumed high dissolved oxygen concentrations in a short period of time, while the refractory detritus generated 2,3 times lower oxygen demand. Thus, those detritus tend to accumulate on the Óleo lagoon sediment and generate, in a long term, low dissolved oxygen demands until they became a permanent sediment compound. The S. auriculata experiment indicated that during the detritus aerobic decomposition (that occurs on the sediment superficial layers) the bentonic oxygen demand did not increased by the presence of microorganisms and nutrients discharged by the sediment. Regarding the detritus age, 180 days decomposition seems to be enough to observe changes in the consumed dissolved oxygen, since it was possible to observe a smaller DO consumption in those detritus decomposition when compared with younger detritus. The previous decomposition under aerobic conditions influenced the rate of the oxygen consumption process; pre-decomposed detritus under anaerobic conditions presented higher kD values, probably related to the higher fiber disaggregation. Thus, the changes in the oxygenation conditions that can occur on the lagoon sediment surface could modify the aerobic decomposition rates, and, as a consequence, the oxygen consumption of macrophytes decomposition half-life times.